2019
DOI: 10.4049/jimmunol.1801303
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosisInhibits Autocrine Type I IFN Signaling to Increase Intracellular Survival

Abstract: The type I IFNs (IFN-a and-b) are important for host defense against viral infections. In contrast, their role in defense against nonviral pathogens is more ambiguous. In this article, we report that IFN-b signaling in murine bone marrow-derived macrophages has a cell-intrinsic protective capacity against Mycobacterium tuberculosis via the increased production of NO. The antimycobacterial effects of type I IFNs were mediated by direct signaling through the IFN-a/b-receptor (IFNAR), as Abmediated blocking of IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 74 publications
4
26
1
1
Order By: Relevance
“…The role of IFIT family during Mtb infection remains unknown. In contrast to our observation of IFIT1 upregulation in AMs, a recent study showed that the IFIT1 gene was one of the most downregulated genes in murine BMDMs infected with Mtb H37Rv for 4 days (64). Although no anti-mycobacterial effects were attributed to IFIT1, an early anti-or pro-mycobacterial effect depending on Mtb strain or virulence and macrophage species cannot be ruled out.…”
Section: Ams Of Tb Patients Respond To Infection With Virulent Mtb CLcontrasting
confidence: 99%
“…The role of IFIT family during Mtb infection remains unknown. In contrast to our observation of IFIT1 upregulation in AMs, a recent study showed that the IFIT1 gene was one of the most downregulated genes in murine BMDMs infected with Mtb H37Rv for 4 days (64). Although no anti-mycobacterial effects were attributed to IFIT1, an early anti-or pro-mycobacterial effect depending on Mtb strain or virulence and macrophage species cannot be ruled out.…”
Section: Ams Of Tb Patients Respond To Infection With Virulent Mtb CLcontrasting
confidence: 99%
“…8A), suggesting that while Lrrk2 KO macrophages can control Mtb replication early after infection, they are more permissive for replication once the bacteria have established a niche. These results are consistent with a recent report demonstrating that defective IFNAR signaling in BMDMs leads to increased Mtb replication (Banks et al, 2019).…”
Section: Lrrk2 Ko Mice Can Control Mtb Replication But Have Exacerbatsupporting
confidence: 94%
“…Mtb is a potent activator of cytosolic DNA sensing (Manzanillo et al, 2012;Watson et al, 2012), and type I IFN is an important biomarker of Mtb infection associated with poor outcomes in humans and in mouse models of infection (Berry et al, 2010). New insights into the requirement of IFNAR signaling for nitric oxide production in macrophages ex vivo, suggest critical roles for type I IFN induction in cell-intrinsic control of Mtb replication (Banks et al, 2019). However, the degree to which these macrophage phenotypes translate to mouse models of infection remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, deletion of nucleotides TCC in human IFNAR1 (human SNP rs72552343) increases resistance to Mtb (Zhang et al, 2018), as does IFNAR1 deletion in mice ( Ifnar1 −/−) (Mayer-Barber et al, 2014). Type I IFN can exert antimicrobial activity in murine macrophages; however, this effect depends on the production of nitric oxide, which is not consistently associated with a reduced mycobacterial burden in human cells (Banks et al, 2019; Thoma-Uszynski et al, 2001). In our study, perturbations of type I IFN signaling improved host cell survival, decreased bacterial load in both M. bovis BCG and Mtb infections, and interfered with the induction of anti-inflammatory cytokines, e.g., IL-10 and IL-1Ra.…”
Section: Discussionmentioning
confidence: 99%